Visualizing Enzyme Secretion from Individual Barley (Hordeum vulgare) Aleurone Protoplasts. - Hillmer, S. (1993)
A method was developed to detect [alpha]-amylase gene expression and [alpha]-amylase secretion from individual barley (Hordeum vulgare L. cv Himalaya) aleurone protoplasts. Protoplasts are incubated in liquid media with or without hormones and embedded in a thin film of agarose and starch, where they remain viable for up to 24 h. [alpha]-Amylase secreted by individual protoplasts digests the starch, and starch hydrolysis is visualized after 45 min by staining the preparation with I2KI. After I2KI staining, secreting protoplasts are surrounded by a clear, starch-free halo visible by light microscopy. The formation of starch-free halos is dependent on the synthesis and secretion of [alpha]-amylase and is not caused by carry-over of preformed enzyme from incubation media. Treating protoplasts with inhibitors of protein synthesis or exposing them to anaerobic conditions for 2 h before embedding them in agarose prevents the formation of halos. When [alpha]-amylase secretion is observed by counting the percentage of secreting protoplasts, the data are comparable to that obtained by measuring [alpha]-amylase secretion from a population of cells. The response of individual protoplasts to gibberellic acid (GA3) and abscisic acid measured by the thin-film method is almost identical to the response of populations of protoplasts to these hormones, validating the utility of this method. Although not generally practical for quantifying secretion, the thin-film method is uniquely useful in distinguishing secreting from nonsecreting protoplasts. In none of our experiments did more than 60% of the protoplasts secrete [alpha]-amylase when exposed to GA3, even though more than 95% of the protoplasts in the preparations were viable. Similar results were obtained when the response to GA3 was assayed at the level of gene transcription by visualizing the transient expression of a plasmid containing the promoter from [alpha]-amylase fused to the reporter gene glucuronidase in single protoplasts. The thin-film secretion assay also revealed that the response of a population of protoplasts to GA3 was not uniform with time. The effect of GA3 treatment was to gradually increase the percentage of responding protoplasts up to a maximum of 50 to 60%. Abscisic acid, which inhibits [alpha]-amylase secretion by GA3-treated protoplasts, reduced the proportion of protoplasts that secrete the enzyme.